Quality participation experiences in the physical activity domain: Perspectives of veterans with a physical disability. (March 2017) - Shirazipour, Celina H.; Evans, M. Blair; Caddick, Nick; Smith, Brett; Aiken, Alice B.; Martin Ginis, Kathleen A.; Latimer-Cheung, Amy E.
Abstract: Objectives: An important consideration for physical activity (PA) participation for individuals with a physical disability, including veterans, is that opportunities exist for full participation. Full participation can be understood as both the quantity and quality of participation. The objective of this study is to explore perceptions of a quality PA experience for military veterans with a physical disability. Design: Qualitative semi-structured interviews were conducted to explore perspectives of a quality PA experience. Method: Eighteen veterans (15 men, 3 women) with a physical disability were recruited using maximum variation sampling to take part in interviews. The interviews explored their PA experiences, with a focus on exploring participants' perspective of a quality PA experience. Data were analyzed using thematic analysis. Results: Two overarching themes, elements of a quality experience and conditions enabling access to a quality experience, were identified. Within the overarching theme of elements of a quality experience, four key themes were identified: group cohesion, challenge, having a role, and independence and choice. A further three key themes (the physical and social environments, and program structure) were identified within the overarching theme of conditions for accessing the quality experience. Conclusion: The findings both support and extend previous conceptualizations of quality participation. They provide insight into context-specific understandings of quality for PA and veterans. More broadly, the study contributes towards the literature on adapted PA participation, and provides a framework for practitioners aiming to foster quality PA experiences. Highlights: Quality elements of participation are identified, as well as methods for fostering elements. Quality elements include group cohesion, challenge, having a role, and independence and choice. Certain conditions, such as environmental and program features, enable access to quality experiences.